Free Cash Flow, Leverage, Ukuran Perusahaan, dan Manajemen Laba di Perusahaan LQ45 BEI - Bailaen, Mariani Katjie Lenanti; Nugroho, Paskah Ika (E-Jurnal Akuntansi, 2023)
Profit information is generally used as an appraisal of management performance. Earnings information can be used as a target of earnings management. The aim of the research is to empirically test the influence of free cash flow, leverage and company size on earnings management. This research uses LQ45 companies on the 2018-2021 BEI. The technique for collecting data uses purposive sampling which produces 20 LQ45 companies. The analysis method uses multiple linear analysis. The research results show that earnings management is not significantly influenced by free cash flow, while earnings management is significantly positively influenced by leverage and company size. This research contributes to consideration of investor and company management decision making regarding earnings management. Keywords: Earnings Management; Free Cash Flow; Leverage; Firm Size